Peritoneal infections in patients on long-term peritoneal dialysis before and after human cadaveric renal transplantation - Leigh, D. A. (1969)
Long-term peritoneal dialysis was carried out on 38 patients awaiting human cadaveric renal transplantation. Fifty-eight per cent of patients developed infection before transplantation and 41% of those requiring dialysis after transplantation became infected. Infection did not usually occur before the third day of dialysis and 26% of patients developed their first episode of infection in the first week. Almost 50% of patients had only a single episode of infection. The overall rate of infection per 100 patient days of dialysis was 1·23 before transplantation and 4·17 after transplantation. The commonest infecting organisms were Staph aureus and Staph albus and these organisms were frequently isolated from the skin around the dialysis catheter before the infection occurred. Gram-negative infections were more commonly seen after transplantation. Sixty-five per cent of the infections responded to a single course of antibiotic therapy administered in the dialysis fluid. After transplantation Gram-negative infections were usually associated with severe complications and were a major cause of death. Peritoneal dialysis is a convenient way of maintaining patients with chronic renal failure before human cadaveric renal transplantation, and infection, although common is not inevitable, provided precautions are taken to ensure that the dialysis procedure is carried out using aseptic techniques and prophylactic therapy is applied to the skin around the dialysis catheter.